2019
DOI: 10.1172/jci125366
|View full text |Cite
|
Sign up to set email alerts
|

Fra-2–expressing macrophages promote lung fibrosis

Abstract: at. tocol YER-2002245-031416GN). The protocol was also carried out in strict accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals (National Academies Press, 2011). The project design to obtain human samples was approved by the ethical committee of the Instituto de Salud Carlos III (Madrid, Spain). In addition, samples and/or data from patients included in this study were provided by the Biobanco i+12 in the Hospital 12 de Octubre integrated in the Spanish Hospital Biobank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 75 publications
2
54
2
Order By: Relevance
“…We therefore hypothesized that ILC3-derived GM-CSF might not only inhibit a fibroblast/myofibroblast-like phenotype in macrophages, but also their ability to stimulate mesenchymal cells. In keeping with this, colonic macrophages from ILC-depleted mice showed an increase in Col6a1 , Col6a2 , and Col6a3 transcripts ( Figure 6 B) that together form trimers that make up collagen type VI, previously shown to promote myofibroblast activation in the context of lung fibrosis ( Ucero et al., 2019 ). We also found a marked increase in several growth factor transcripts in colonic macrophages ( Figure 6 F) and colonic levels of Pdgfb were globally elevated in the absence of ILCs ( Figure S6 E).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We therefore hypothesized that ILC3-derived GM-CSF might not only inhibit a fibroblast/myofibroblast-like phenotype in macrophages, but also their ability to stimulate mesenchymal cells. In keeping with this, colonic macrophages from ILC-depleted mice showed an increase in Col6a1 , Col6a2 , and Col6a3 transcripts ( Figure 6 B) that together form trimers that make up collagen type VI, previously shown to promote myofibroblast activation in the context of lung fibrosis ( Ucero et al., 2019 ). We also found a marked increase in several growth factor transcripts in colonic macrophages ( Figure 6 F) and colonic levels of Pdgfb were globally elevated in the absence of ILCs ( Figure S6 E).…”
Section: Resultssupporting
confidence: 81%
“…Remarkably, depletion of ILCs or neutralization of GM-CSF in the context of enteropathic infection or barrier breach-induced inflammation resulted in enhanced expression of collagen subunits by macrophages, as well as production of fibroblast-stimulating growth factors, including PDGF-BB. Macrophage production of collagen has been previously described in human macrophages in vitro and in atherosclerotic plaques ( Schnoor et al., 2008 ; Weitkamp et al., 1999 ), in mouse models of kidney ( Meng et al., 2016 ) and lung injury ( Ucero et al., 2019 ), and in skin wounds ( Sinha et al., 2018 ), consistent with a transition to a fibroblast/myofibroblast phenotype. Indeed, in the latter study, fate-mapping suggested that two-thirds of granulation tissue fibroblasts in the wound were of myeloid origin ( Sinha et al., 2018 ).…”
Section: Discussionmentioning
confidence: 87%
“…Upon survey of the transcriptomes of Mo-AMs and TR-AMs from mice that were treated intratracheally (i.t.) with bleomycin, we were particularly interested in ApoE because (a) it is one of the most differentially expressed genes in Mo-AMs as compared with TR-AMs from bleomycin-treated lungs and (b) its abundance in Mo-AMs is much greater than several previously defined profibrotic mediators in this AM subtype, such as PDGF and Collagen VI (10,23,24).…”
Section: Resultsmentioning
confidence: 99%
“…The only other mouse model purported to represent CTD‐PAH is the Fra‐2–Tg mouse . While that model does share many features with scleroderma, Fra‐2–Tg mice have severe lung fibrosis and inflammation with associated pulmonary hypertension more akin to World Health Organization group III pulmonary hypertension. Moreover, Fra‐2–Tg mice have a much lower RVSP elevation (RVSP ~30 mm Hg) than TNF‐Tg mice (RVSP 50–100 mm Hg).…”
Section: Discussionmentioning
confidence: 99%